Eksplorasi Mainan Seni Dengan Pendekatan Berbasis Praktik - Fadhillah, Alam; Hadi Prayitno, Eko (Program Studi Pendidikan Seni Rupa FBS UNJ, 2023)
Toys as a Media for Self-Emotional Representation, Thesis for Creation of Fine Arts, Department of Fine Arts Education. Faculty of Languages and Arts, State University of Jakarta. An art or designer toy is a product made by artists and designers who are self- produced or made by small, independent toy companies, usually in very limited editions. A personal journal is made, designed by carrying the concept of telling stories and expressing each emotion through sketch images, summarizing various sketches that have been made into one character that represents these emotions during the work, 3D modeling and printing with 3D printing tools. Responding to the trend of pop culture by contributing to the creation of Art Toys, nowadays many toy designers are starting to make their own characters into art toys, the product can be judged in an authentic style as a toy product targeted at adults. The product is designed based on surveys and input on the needs of the community and has been tested among the upper middle class starting from early adulthood in the Jakarta area as a target market. Of course, this art toy product will be an option as well as an answer to pop culture trends and provide education about psychological conditions, especially in emotional disorders, as a work of art or a collection of art toy products can last for an indefinite period depending on the treatment technique.